A Southern Girl : A Novel - Warley, John (Book collections on Project MUSE., 2014)
Set against the exquisite, historical backdrop of Charleston's insular South of Broad neighborhood, A Southern Girl is a tale of international adoption and of families lost, then found anew through revelations, courage, and the perseverance of a love without bounds. With two biological sons and a promising career, Coleman Carter seems set to fulfill his promise as a resourceful trial lawyer, devoted husband, and dutiful father until his wife, Elizabeth, champions their adoption of a Korean orphan. This seemingly altruistic mission estranges Coleman's conservative parents and demands that he now embrace the unknown as fully as he has always entrenched himself in the familiar. -- -- The first release from Pat Conroy's Story River Books, A Southern Girl includes a foreword by New York Times bestselling novelist Therese Ann Fowler.